Critical factors in cocksfoot (Dactylis glomerata L.) panicle production in Finland and the implications for seed production - Niemeläinen, Oiva (fi, 1991)
The main factors affecting cocksfoot panicle production negatively in Finland were divided in three categories. Firstly, the juvenile stage of cocksfoot and a short favourable for floral evocation in the fall caused inadequate floral evocation. Therefore the panicle production in the first harvest year remained small when the stand was sown late in the previous season or was established with a late maturing cover crop. Secondly, damages due to low temperatures in the absence of snow cover and/or ice cover during winter decreased panicle and seed production. Thirdly, frosts during panicle growth stage destroyed panicles and decreased the seed yield. In addition, a long snow cover period may have decreased the seed yield since d tended to be higher when the snow cover period iin the previous winter was shorter than 120. The cultivar strongly affected the ability of a stand to produce panicles in Finnish conditions. The choice of cultivar is important for abundant panicle production. The average seed yield of the standard cv. Haka was 258 kg ha-1 (range from 0eltivar trials at the Agricultural Research Centre.. The average yield per hectare could be raised by establishing the stands without a cover crop early in the growing season. The present situation in Finland with obligatory fallow makes this kind of establishment recommendable. If the stands established with a late maturing cover crop, the yield of first year stand should be taken for fodder and the second year harvest for seed. Fodder and seed production of cocksfoot should be combined since a seed production stand can give a fodder yield in addition to a seed yield. Combination of fodder and seed production would be important because the fodder yield of the stand can still be high although panicle production, and consequently, seed production fails. Seed production areas where the risk of late spring frost is high should be astised on areas where the risk of ice cover and low temperatures in absence of snow cover is small. However, a long snow cover period is also detrimental for the panicle production. The southern Lake District area in Eastern Finland may have favourable climatic conditions for seed production of cocksfoot, therefore seed production should be tried that area.
Keywords: Ka; koiranheinä; Dactylis glomerata; nurmikasvit; siementuotanto; orchard grass; seed production; stress; cultivar; variety; floral evocation; induction; yield losses